The Effect of High-Intensity Interval Training on Cardiovascular Endurance (VO₂max) in Badminton Athletes at Mahmuda Club, Padang - Yuni Rahmah; Wilda Welis; Ahmad Chaeroni; Fahd Mukhtarsyaf (Jurnal Master Penjas & Olahraga, 2026)
This study aims to determine the effect of high-intensity interval training (HIIT) on the cardiovascular endurance (VO₂Max) of badminton athletes from the Mahmuda Club in Padang. The research method used was an experimental study with a one-group pretest-posttest design. The study sample consisted of 10 athletes. The instrument used in this study was the Multistage Fitness Test (Bleep Test) to measure VO₂Max. Data analysis employed a paired-sample t-test. The results indicated an increase in the mean VO₂Max value from 34.96 at the pretest to 36.29 at the posttest. Based on the statistical test results, a significance value (Sig. 2-tailed) of 0.000 < 0.05 was obtained, indicating that there is a significant effect of high-intensity interval training (HIIT) on the improvement of cardiovascular endurance (VO₂Max) in athletes. Thus, the high-intensity interval training (HIIT) method is effective for improving the cardiovascular endurance of badminton athletes.